An orthopedic implant with tantalum coating on the surface and a preparation method thereof

By plating tantalum coating on the surface of orthopedic implants and heat treatment, the problems of poor wear resistance and harmful element release of existing implants are solved, and the biocompatibility and comprehensive performance of the implants are significantly improved.

CN116334542BActive Publication Date: 2025-04-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310279153.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-04-11
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

Existing orthopedic implants such as TC4 titanium alloy, cobalt-chromium molybdenum and stainless steel are subject to poor wear resistance and harmful metal ions release, resulting in tissue damage and impaired immune function, limiting their application in orthopedic implant field.

Method used

The magnetron sputtering method is used to coat the tantalum coating on the surface of the implant, and the bonding force between the coating and the substrate is improved by heat treatment, thereby enhancing the hardness, wear resistance and corrosion resistance of the implant.

Benefits of technology

The implant surface is formed with tissue-friendly tantalum plating, which improves the binding force between the plating and the substrate, prevents the seepage of harmful elements, and improves the biocompatibility and comprehensive mechanical properties of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334542B_ABST
    Figure CN116334542B_ABST
Patent Text Reader

Abstract

The present invention relates to a surface modification technology for orthopedic implants, and discloses an orthopedic implant with a tantalum coating on the surface and a preparation method thereof, comprising: step 1, cleaning the implant device to be plated; step 2, sputtering the device surface under vacuum conditions using a pure Ta target; step 3, vacuum heat treating the coated device to obtain a finished product, and the heat treatment temperature is 650-1000°C. The present invention uses a magnetron sputtering method to deposit Ta coatings of different thicknesses, and uses a specific temperature for heat treatment, so that the Ta element of the coating diffuses with the matrix, improves adhesion, and prevents the exudation of harmful elements in the alloy in the tissue, while improving the tissue compatibility of the device, especially the compatibility with osteoblasts, and promoting the effect of tissue healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface modification technology for orthopedic implants, and in particular to an orthopedic implant with a tantalum coating on the surface and a preparation method thereof. Background Art

[0002] With the development of medical technology, the demand for orthopedic implant materials is increasing, and titanium alloys are widely used in orthopedic medicine for replacement, correction, fixation, etc. Among them, metal materials represented by TC4 titanium alloy, cobalt-chromium-molybdenum and medical stainless steel have the advantages of high strength and easy processing and molding, and are widely used in orthopedic implant materials, such as artificial bones, artificial joints, tooth roots, bone plates, bone nails, etc. During use, it was found that due to poor wear resistance between TC4 titanium alloy, cobalt-chromium-molybdenum, and stainless steel devices and some host bones, the debris produced will cause tissue damage, which is not conducive to the growth of bone cells, causing aseptic loosening and inflammatory reactions; TC4, cobalt-chromium-molybdenum, and stainless steel devices may release metal ions such as Al, V, Cr, Co, and Mo in body fluids, which may cause local immune dysfunction, allergies, and poisoning. This makes the application of titanium alloys, cobalt-chromium-molybdenum, stainless steel and other metals in the field of orthopedic implants subject to certain restrictions.

[0003] Tantalum (Ta) has high osteogenic properties, can induce osteoblast differentiation, and promote bone fusion. It has been developed and applied in plastic surgery and other surgical disciplines. However, the application of Ta materials is limited due to its high price, high density, and difficulty in processing.

[0004] At present, the technologies for depositing Ta coating on the surface of TC4, CoCrMo alloy and stainless steel include plasma spraying, sol-gel method, laser cladding, chemical vapor deposition and PVD. Due to the large difference in thermal expansion coefficient and elastic modulus between the deposited Ta coating and TC4 titanium alloy, CoCrMo alloy and stainless steel, the coating is easy to peel off, which has become the main obstacle to the application of this technology.

[0005] CN106691609A discloses a highly tissue-affinity and corrosion-resistant dental implant, which uses a combination of titanium coating, pure tantalum coating, and tantalum composite coating to obtain a dental implant with good tissue affinity and corrosion resistance, and the coating and the substrate are well bonded. A variety of composite layers and doping methods are used, but the bonding strength between the substrate and the coating is still average.

[0006] CN112813404A discloses a tantalum coating, a preparation method thereof and a dental implant, which adopts a chemical vapor infiltration method to form a tantalum coating on the surface of a workpiece. The substrate and the coating layer have good bonding strength, but the required temperature is extremely high. The tantalum material needs to be heated to 6000-6300°C, which has extremely high requirements for equipment and experimental conditions, and also has high requirements for the material of the implanted device, making industrialization difficult. Summary of the invention

[0007] The present invention solves the problem that the implant has poor tissue compatibility, and the conventional tantalum coating has weak bonding strength with the substrate and is easy to peel off. A method is provided for coating a tantalum coating on the surface of a titanium alloy, a cobalt-chromium-molybdenum alloy, or a stainless steel implant device by a magnetron sputtering method and improving the bonding strength of the coating by heat treatment. The hardness, wear resistance, and corrosion resistance of the implant device are also significantly improved. The method forms a tissue-friendly tantalum coating on the surface of the implant device, and the coating has good metallurgical bonding with the device substrate. The permeation of harmful elements in the alloy into the tissue is hindered, and at the same time, the tissue compatibility of the device, especially the compatibility with osteoblasts, is improved, and tissue healing is promoted.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing an orthopedic implant with a tantalum coating on its surface comprises the following steps:

[0010] Step 1, cleaning the implant device to be plated;

[0011] Step 2, sputtering the device surface with pure Ta target material;

[0012] Step 3, subjecting the coated device to vacuum heat treatment to obtain a finished product, with the heat treatment temperature being 650-1000°C.

[0013] The present invention uses a magnetron sputtering method to deposit Ta coatings of different thicknesses, and uses a specific temperature for heat treatment so that the Ta element of the coating and the substrate diffuse mutually, thereby improving adhesion. By controlling the heat treatment temperature, a coating structure mainly based on an alpha-Ta structure is obtained. By controlling the heat treatment process, the diffusion depth is controlled, thereby ensuring that the mutual diffusion is sufficient to improve the coating bonding strength without affecting the performance of the coating and the substrate material, and at the same time inhibiting the release of toxic metal ions in TC4 titanium alloy, CoCrMo alloy, and stainless steel, thereby improving the compatibility of implanted devices with tissues.

[0014] The implant device coating and substrate are mechanically bonded, which is prone to peeling. Through heat treatment, the elements between the Ta coating and the substrate can be diffused to improve the bonding strength between the coating and the substrate. Excessively high temperature and excessively long heat treatment can easily cause excessive growth of the diffusion layer, leading to cracking of the Ta film. If the heat treatment temperature is too low or the time is too short, a certain degree of diffusion effect will not be achieved.

[0015] Further preferably, when the implant device substrate is titanium alloy, the heat treatment temperature is 700-800°C; when the implant device substrate is cobalt-chromium-molybdenum alloy, the heat treatment temperature is 850-950°C; when the implant device substrate is stainless steel, the heat treatment temperature is 900-1000°C.

[0016] Through heat treatment, the biocompatibility of implant devices can be improved and implant devices can be given better comprehensive mechanical and chemical properties; moreover, the organizational structure of the surface coating of the implant device after heat treatment becomes more dense and uniform, which can reduce the micropore defects on the coating surface and hinder the path of corrosive solution through the coating, thereby improving the corrosion resistance of the implant device substrate, effectively avoiding large-scale shedding of the coating, reducing the friction surface area, and improving the friction performance of the implant device substrate.

[0017] Vacuum degree of heat treatment <1.0×10 -3 Pa, the heat treatment time is 1-5h; since the tantalum coating prepared by magnetron sputtering has defects such as tiny micropores, poor bonding strength and poor biocompatibility on the surface, this may not be sufficient to meet medical applications. For this reason, the vacuum heat treatment process can be used to effectively reduce the stress at the interface and improve the bonding strength of the coating on the surface of the implant device. At the same time, the grains are refined, which is beneficial to reduce the defects of micropores and increase the density of the tissue, thereby further improving the corrosion resistance and biocompatibility of the implant device substrate.

[0018] In some embodiments, the heating rate is 3-10°C / min. In some embodiments, the heating rate is set to 5°C / min, mainly because a faster heating rate causes greater internal stress in the film, which is not conducive to improving the bonding strength of the coating, and the defects caused by the film density deteriorate, while a lower heating rate easily causes the film grains to become larger, prompting the formation of columnar crystal "nuclei", large and small grains appear on the surface, and the coating structure deteriorates and becomes uneven.

[0019] Preferably, in step 1, inert gas plasma cleaning is used, such as argon plasma cleaning. After surface cleaning, surface oil stains are removed, and the device can be rotated during the cleaning process so that all parts can be completely cleaned.

[0020] The sputtering conditions include: the distance between the device surface and the target center is 100 mm, and the device rotates continuously during the sputtering process; the distance between the device surface and the target center is 50-150 mm, and the device rotates continuously during the sputtering process; the back vacuum during coating is <1.0×10 -3 Pa; preferably, the distance between the device surface and the target center is 100 mm.

[0021] When a target with a diameter of 100 mm is used, the power applied to the target is 300-500 W, and the corresponding sputtering current is 0.5-1.5 A; the coating time is 4-8 hours, and the thickness of the Ta coating is 1-20 μm; if a target of other sizes is used, the power applied to the target and the coating time need to be adjusted accordingly.

[0022] Preferably, the device is heated and biased during the coating process to improve the bonding strength between the coating and the substrate; the heating temperature is 150-210°C, and the bias is -200 to -100V. The temperature of the deposited coating should not be too high or too low. When the deposition temperature is high, the grain size of the coating increases, which is not conducive to the compactness of the coating. Too low a deposition temperature causes the internal stress of the coating to be large, and the crystallinity of the coating to be reduced, which is not conducive to the bonding strength of the coating. A suitable deposition temperature can improve the deposition quality and density of the coating. The bias voltage in this design is conducive to improving the columnar crystal structure of the coating under a suitable bias voltage, making the coating structure more dense and uniform.

[0023] The purity of the pure Ta target material is not less than 99.95%.

[0024] If the thickness of the Ta coating is too thin, it is not conducive to improving the biocompatibility of the implant, and if it is too thick, the coating is prone to fall off. Preferably, the thickness of the Ta coating is 1-20 μm; in some embodiments, the thickness is 4-10 μm. The various properties of tantalum coatings of different thicknesses also show certain differences.

[0025] The invention also provides an implant with a tantalum coating on the surface. The tantalum coating is plated on the surface of the implant by adopting the method.

[0026] The bonding strength between the tantalum coating and the substrate in the implant prepared by the present invention is not less than 15N;

[0027] In some embodiments, L929 cells and MC3T3-E1 cells are used to demonstrate its biocompatibility, and the cell proliferation rate of the plant milk is not less than 100%.

[0028] The inventors have found through experimental research that the heat treatment temperature can not only enhance the bonding strength between the substrate and the tantalum coating, but also has different effects on the hardness, elastic modulus, friction performance, and electrochemical corrosion of the implant samples, and also has different degrees of influence on the biocompatibility of the implant samples. The effects are not completely uniform. When the bonding strength is good, the hardness or biocompatibility may not be ideal.

[0029] In some embodiments, when the implant substrate is made of TC4, the heat treatment temperature is 725-775°C; when the heat treatment temperature is in the range of 700-800°C, the sample has the best combination of the bonding strength between the substrate and the tantalum coating, hardness, friction performance, corrosion performance and biocompatibility. In some embodiments, when the implant substrate is made of TC4, the heat treatment temperature is 750°C.

[0030] In some embodiments, when the implant substrate is made of cobalt-chromium-molybdenum, the heat treatment temperature is 875-925°C, and the sample has the best combination of bonding strength between the substrate and the tantalum coating, hardness, friction performance, corrosion performance and biocompatibility. In some embodiments, when the implant substrate is made of cobalt-chromium-molybdenum, the heat treatment temperature is 900°C.

[0031] In some embodiments, when the implant device substrate is stainless steel, the heat treatment temperature is 925-975°C, and the device has the best comprehensive performance. In some embodiments, when the implant device substrate is stainless steel, the heat treatment temperature is 950°C.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention is directed to a method for coating implantable devices such as titanium alloys, cobalt-chromium-molybdenum alloys, and stainless steel with tantalum coatings and improving the coating bonding strength through heat treatment. The method forms a tissue-friendly tantalum coating on the surface of the implantable device, and the coating has a good metallurgical bond with the device substrate, which hinders the infiltration of harmful elements in the alloy into the tissue, while improving the cell and tissue compatibility of the device, especially the compatibility with osteoblasts, and promoting tissue healing. In addition, a suitable heat treatment process can also improve the mechanical properties of the device surface hardness, corrosion resistance, wear resistance, etc. The preparation process is simple, does not require abnormal high temperature conditions, has more moderate requirements on equipment and preparation costs, and is more conducive to industrial implementation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Cross-sectional morphology and corresponding energy spectrum analysis of TC4 samples plated with 4.3 μm Ta at different heat treatment temperatures: (a) room temperature; (b) 650°C; (c) 750°C; (d) 850°C.

[0035] Figure 2 Cross-sectional morphology and corresponding energy spectrum analysis of TC4 samples plated with 9.5 μm Ta at different heat treatment temperatures: (a) room temperature; (b) 650°C; (c) 750°C; (d) 850°C.

[0036] Figure 3 Cross-sectional morphology and corresponding energy spectrum analysis of 4.3 μm Ta-plated Cobalt-Cr-Mo samples at different heat treatment temperatures: (a) room temperature; (b) 800°C; (c) 900°C; (d) 1000°C.

[0037] Figure 4 Cross-sectional morphology and corresponding energy spectrum analysis of 9.5 μm Ta-plated Cobalt-Cr-Mo samples at different heat treatment temperatures: (a) room temperature; (b) 800°C; (c) 900°C; (d) 1000°C.

[0038] Figure 5XRD patterns of TC4 samples with Ta 4.3μm coating and without Ta coating at different heat treatment temperatures.

[0039] Figure 6 XRD patterns of Ta-plated 9.5μm Ta and unplated TC4 samples at different heat treatment temperatures.

[0040] Figure 7 XRD patterns of Ta 4.3μm and un-Ta-plated Co-Cr-Mo samples at different heat treatment temperatures.

[0041] Figure 8 XRD patterns of Ta 9.5μm plated and unplated Co-Cr-Mo samples at different heat treatment temperatures.

[0042] Fig. 9 (a) Nanoindentation hardness and (b) elastic modulus of TC4 samples with and without 4.3 μm Ta coating at different heat treatment temperatures.

[0043] Fig.10 (a) Nanoindentation hardness and (b) elastic modulus of TC4 samples with and without 9.5 μm Ta coating at different heat treatment temperatures.

[0044] Fig.11 (a) Elastic modulus and (b) nanoindentation hardness of CoCrMo samples with and without 9.5 μm Ta coating at different heat treatment temperatures.

[0045] Fig.12 Scratch curves and corresponding scratch morphologies of TC4 samples plated with Ta 4.3μm at different heat treatment temperatures: (a) room temperature; (b) 650℃; (c) 750℃; (d) 850℃ and (e) sliding distance and critical load during sample wear.

[0046] Fig.13 Scratch curves and corresponding scratch morphologies of TC4 samples plated with Ta 9.5μm at different heat treatment temperatures: (a) room temperature; (b) 650℃; (c) 750℃; (d) 850℃ and (e) sliding distance and critical load during sample wear.

[0047] Fig.14 Scratch curves and corresponding scratch morphologies of CoCrMo samples plated with Ta 4.3μm at different heat treatment temperatures: (a) room temperature; (b) 650℃; (c) 750℃; (d) 850℃ and (e) critical scratch distance and load.

[0048] Fig.15Scratch curves and corresponding scratch morphologies of CoCrMo samples plated with Ta 9.5μm at different heat treatment temperatures: (a) room temperature; (b) 650℃; (c) 750℃; (d) 850℃ and (e) critical scratch distance and load.

[0049] Fig.16 The friction coefficient curve of TC4 sample plated with 4.3μm Ta after heat treatment at different temperatures.

[0050] Fig.17 The friction coefficient curve of TC4 sample plated with 9.5μm Ta after heat treatment at different temperatures.

[0051] Fig.18 This is the friction coefficient curve of the Co-Cr-Mo sample plated with 4.3μm Ta after heat treatment at different temperatures.

[0052] Fig.19 This is the friction coefficient curve of the Co-Cr-Mo sample plated with 9.5μm Ta after heat treatment at different temperatures.

[0053] Fig. 20 Electrochemical corrosion test results of 4.3 μm Ta-plated and unplated TC4 samples in SBF solution at different heat treatment temperatures, (a) polarization curves, (b) Nyquist plots.

[0054] Fig.21 Electrochemical corrosion test results of 9.5μm Ta-plated and unplated TC4 samples in SBF solution at different heat treatment temperatures, (a) polarization curves, (b) Nyquist plots.

[0055] Fig. 22 Polarization curves of 4.3μm Ta-plated and unplated CoCrMo samples in SBF solution at different heat treatment temperatures.

[0056] Fig.23 Polarization curves of 9.5μm Ta-plated and unplated CoCrMo samples in SBF solution at different heat treatment temperatures.

[0057] Fig.24 Relative proliferation rates of MC3T3-E1 cells cultured in 100%, 50%, and 25% extracts at different heat treatment temperatures for different time periods: (a) 1 day; (b) 2 days; (c) 3 days.

[0058] Fig.25 Relative proliferation rates of MC3T3-E1 cells cultured in 100%, 50%, and 25% extracts at different heat treatment temperatures for different time periods: (a) 1 day; (b) 2 days; (c) 3 days.

[0059] Fig.26 Changes in the proliferation rate of L929 cells in Ta-coated and uncoated CoCrMo alloys: (a) uncoated CoCrMo at room temperature; (b) CoCrMo / Ta 4.3μm; (c) CoCrMo / Ta 9.5μm; (d) CoCrMo / Ta 4.3μm 900℃; (e) CoCrMo / Ta 9.5μm 900℃; (f) blank control group and (g) cell proliferation rate.

[0060] Fig. 27 Changes in the proliferation rate of MC3T3-E1 cells of CoCrMo alloys with and without Ta coating: (a) uncoated CoCrMo at room temperature; (b) CoCrMo / Ta 4.3μm; (c) CoCrMo / Ta 9.5μm; (d) CoCrMo / Ta 4.3μm 900℃; (e) CoCrMo / Ta 9.5μm 900℃; (f) blank control group and (g) cell proliferation rate. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0062] The raw materials used in the following specific embodiments were purchased from the market. The TC4 titanium alloy and CoCrMo alloy matrix materials used in the experiment were purchased from Baoti Group Co., Ltd. and Tangshan Qizheng Technology Co., Ltd., respectively. The sizes are The target source uses a round Ta target purchased from Zhongnuo New Materials (Beijing) Technology Co., Ltd., with a size of ( Purity 99.95%).

[0063] Example 1

[0064] Using medical titanium alloy TC4 and cobalt-chromium-molybdenum samples as substrates, a tantalum coating is plated on the surface thereof, and the specific steps include:

[0065] Step 1: Place the substrate and glass sheet in a vacuum chamber and evacuate the chamber to a vacuum of <1×10 -3 Pa, through Ar + The samples were ion cleaned by plasma for 30 min (Ar gas pressure 0.35 Pa, Ar gas flow rate 70 sccm);

[0066] Step 2, using a round Ta target ( Purity 99.95%), the distance from the center of the sample surface to the center of the target is 100mm, the sample is rotated on the sample stage (rotation speed 30r / min) to obtain a uniformly distributed Ta coating, and the thermocouple for measuring the deposition temperature is placed on the back of a 2mm thick stainless steel sample disk. The deposition temperature is set to 180°C, the negative bias voltage on the substrate is set to 150V (direct current, DC), the sputtering current and power are set to 1A and 400W respectively, and the experimental parameters are listed in Table 1. The coating thickness is controlled by time, and two Ta coatings of 4.3μm and 9.5μm thickness are prepared respectively.

[0067] Table 1: Magnetron sputtering system parameters for depositing Ta coatings

[0068]

[0069] Step 3, heat treatment process

[0070] Through heat treatment, the elements between the coating and the substrate diffuse mutually, thus improving the bonding strength between the coating and the substrate. The coated samples are placed in a vacuum heat treatment furnace and evacuated to <1.0×10 -3 Pa, and then heated at a rate of 5 ° C / min, and kept constant for 5 min every time it increased by 300 ° C, and then continued to rise until the set temperature was reached. The annealing temperatures of TC4 titanium alloy were 650 ° C, 750 ° C and 850 ° C, and the annealing temperatures of CoCrMo alloy were 800 ° C, 900 ° C and 1000 ° C, respectively. The annealing time was set to 5 h. After the annealing, the samples were cooled with the furnace. The processing parameters are shown in Table 2. Tantalum-plated TC4 and cobalt-chromium-molybdenum implants at different heat treatment temperatures were obtained.

[0071] Table 2: Heat treatment process parameters

[0072]

[0073] Testing and analysis

[0074] 1. Surface micromorphology

[0075] 1.1. Microscopic morphology of TC4 sample surface

[0076] Figure 1 and Figure 2 The cross-sectional morphology and corresponding element distribution of the 4.3μm and 9.5μm Ta coatings on the surface of the TC4 sample are shown respectively. The treatments in each figure refer to (a) room temperature (i.e., no heat treatment); (b) 650℃; (c) 750℃; and (d) 850℃.

[0077] from Figure 1 (a) and Figure 2(a) It can be seen that there is a clear interface between the Ta coating and the TC4 titanium alloy substrate, and no microcracks or voids are found in the interface, indicating good interface bonding and deposition quality. At the annealing temperature of 650℃, no obvious mutual diffusion between the Ta coating and the Ti-based elements is observed ( Figure 1 (b) and Figure 2 (b)), as the annealing temperature increases Figure 1 (c, d) and Figure 2 (c, d) A diffusion transition layer appears, and the tantalum element in the coating and the elements of Ti, Al, and V in the matrix diffuse mutually, which helps to improve their chemical affinity, resulting in reduced interface stress and increased interface bonding performance.

[0078] from Figure 1 (c) and Figure 2 (c) Compared to Figure 1 (d) and Figure 2 (d) As for the diffusion between the tantalum coating and the matrix elements, the degree of diffusion is small, and the tantalum coating does not extend deep into the matrix. Figure 1 (c) and Figure 2 (c) It can be seen that the tantalum coating and the Ti-based elements are only initially diffused. EDS analysis shows that the thickness of the inner diffusion layer of the Ta coating modification layer is about 1.50 μm ( Figure 1 c) 1.50 μm ( Figure 2 c), indicating that the thickness of the interdiffusion layer between the two elements is almost the same, with tantalum atoms diffusing inwards and Ti, Al, and V atoms diffusing outwards from the matrix. Figure 1 (d) and Figure 2 (d) The elements in the coating also show the same trend, and the diffusion between the tantalum coating and the Ti-based elements has already reached deep into the matrix, and the thickness of the inner diffusion layer of the tantalum coating is about 10.00 μm ( Figure 1 d) and 12.50 μm ( Figure 2 d), where Figure 2 The coating of (d) shows a thicker interdiffusion layer. Therefore, we know that when the annealing temperature is 750℃, the thickness of the interdiffusion layer of the coating is small ( Figure 1 (c) and Figure 2 (c)), which helps to reduce the stress at the bonding interface and improve the bonding strength between the coating and the substrate. At the annealing temperature of 850℃, the thickness of the diffusion layer of the coating is large ( Figure 1 (d) and Figure 2 (d)), which is not conducive to improving the bonding strength of the coating.

[0079] 1.2. Microscopic morphology of the surface of Cobalt-Chromium-Molybdenum samples

[0080] Figure 3 and Figure 4The cross-sectional morphology and corresponding element distribution of 4.3μm and 9.5μm Ta coatings are shown respectively. The heat treatment temperatures are: (a) room temperature; (b) 800℃; (c) 900℃; (d) 1000℃.

[0081] Figure 3 (a) and Figure 4 (a) shows the cross-sectional morphology and element distribution of the unheat-treated coated CoCrMo sample, respectively. No defects such as pinholes or microcracks in the coating were found at the interface between the coating and the substrate, indicating good deposition quality, which provides a good shielding effect. Figure 3 (b)-(d) and Figure 4 (b)–(d) show the diffusion between the coating and the substrate of the coating samples after heat treatment at 800℃, 900℃ and 1000℃, respectively. The coating after heat treatment has a mutual diffusion effect at the interface, where the coating diffuses into the substrate and the matrix elements diffuse into the tantalum coating. This diffusion is beneficial to eliminate the stress at the interface and improve the bonding strength between the thin film tantalum coating and the substrate surface. Therefore, the process conditions after heat treatment diffusion are very critical to improving the bonding strength between the coating and the substrate.

[0082] 2. Crystal structure of coating

[0083] 2.1 TC4 sample surface coating

[0084] Figure 5 and Figure 6 The XRD patterns of the TC4 titanium alloy samples with tantalum coating prepared in Example 1 after heat treatment at different temperatures are given. Figure 5 Tantalum coating 4.3μm, Figure 6 is 9.5μm. X-ray diffraction studies show that ( Figure 5 , Figure 6 ), the coating initially has a mixture of α-type body-centered cubic lattice structure and β-type metastable tetragonal structure, and no diffraction peak of the matrix is ​​found. Figure 5 It can be seen that with the increase of heat treatment temperature, the diffraction peak height of the (002) plane of the β-Ta phase gradually decreases, while the diffraction peak height of the (110) plane of the α-Ta phase gradually increases, and strong diffraction peaks of α-Ta (211) and β-Ta (513) are found at annealing temperatures of 750℃ and 850℃. The above changes are due to the phase transition from β-Ta to α-Ta coating growth caused by the heat treatment process.

[0085] exist Figure 6It can be found that at a heat treatment temperature of 650°C, two main strong diffraction peaks of β-Ta (002) and (513) planes were observed at 2θ = 33.7° and 71.1°. Since β-Ta exhibits high low-temperature brittleness, this greatly improves the surface hardness value (H) and elastic modulus (E) of the tantalum coating. At a heat treatment temperature of 750°C, the diffraction peaks of α-Ta (110) and (211) planes are very strong, indicating that the microcrystals (texture) in the Ta coating have a preferential curve, and the formation of (110) texture helps to reduce the amount of wear and improve the wear resistance of the coating.

[0086] 2.2 Cobalt-chromium-molybdenum sample surface coating

[0087] Figure 7 and Figure 8 The XRD patterns of 4.3μm and 9.5μm tantalum coatings and bare CoCrMo alloy substrates are shown respectively. The crystal structure of the untreated CoCrMo alloy is mainly composed of α-FCC of (CoCr) and a small amount of ε-(CoCr), and no crystalline phase is detected, while the tantalum coating is mainly composed of a stable body-centered cubic (bcc) phase (α-Ta) and a metastable tetragonal phase (β-Ta). Figure 7 As shown, the Ta coating without heat treatment was coated. Strong peaks appear at 2θ=33.60° and 70.63°, corresponding to the (002) and (513) planes of the (β-Ta) phase, indicating that the preferred orientation of (002) increases, while the 9.5μm tantalum coating sample does not have a strong peak at the corresponding (002) plane. With the increase of annealing temperature, the peak intensity of the (002) plane of the β-Ta phase of the 4.3μm tantalum coating increases, and the peak intensity of the (110) and (211) planes of the a-Ta phase decreases. Figure 8 The peak changes in the 9.5μm tantalum coating also have a similar trend. The a-Ta phase (110) and (211) planes in the 9.5μm tantalum coating have the same decreasing law as the 4.3μm tantalum coating sample, indicating that the annealing temperature has a certain effect on the peak intensity change of the tantalum coating.

[0088] Through SEM and EDS analysis, it can be seen that at an annealing temperature of 750°C, the tantalum coating and the titanium alloy have a certain interdiffusion layer, while cobalt, chromium and molybdenum require a higher annealing temperature (about 900°C) to form a diffusion layer, which is beneficial to improve the adhesion of the coating. After annealing, the tantalum coating is mainly composed of a stable body-centered cubic phase (a-Ta) and a metastable tetragonal phase (β-Ta).

[0089] 3. Mechanical properties of coating

[0090] 3.1 Effect of heat treatment on the surface hardness of TC4 samples

[0091] Fig. 9 and 10The hardness values ​​(H) and elastic modulus (E) of the samples plated with 4.3 μm Ta, 9.5 μm Ta and the corresponding TC4 samples at different heat treatment temperatures measured by nanoindentation are shown, respectively, where (a) is the hardness value and (b) is the elastic modulus. Fig. 9 and 10 It can be seen that the average nanohardness value of the TC4 titanium alloy matrix is ​​(H = 6.1GPa). Compared with the TC4 titanium alloy, the hardness value and elastic modulus of the sample after heat treatment after the tantalum coating are improved. At the annealing temperature of 650°C, the tantalum coating shows the highest hardness value (H = 16.7GPa, 21.7GPa), which is about 2-3 times that of the TC4 titanium alloy matrix, significantly improving the surface hardness of the TC4 titanium alloy matrix. With the increase of annealing temperature, the α-Ta phase (a-Ta dominated coating) increases, resulting in a decrease in hardness and elastic modulus.

[0092] 3.2 Effect of heat treatment on the surface hardness of Cobalt-Chromium-Molybdenum samples

[0093] Fig.11 The average and standard deviation (b) of H (a) and H / E values ​​of the CoCrMo sample coated with 4.3μm and 9.5μm Ta measured by nanoindentation are shown. It can be seen from the figure that with the increase of annealing temperature, the hardness value and H / E ratio of the CoCrMo alloy substrate gradually decrease, while the hardness value and H / E ratio of the coated alloy sample increase significantly compared with the substrate. Fig.11 It can be observed in (a) that with the increase of annealing temperature, the hardness value of the coating alloy sample surface first increases and then decreases, indicating that the sample at 900°C has the highest hardness value, and the hardness value of the 9.5μm Ta coating sample is slightly higher than that of the 4.3μm Tantalum coating sample, which is caused by the increase of β-Ta. Fig.11 (b) It can be seen that the H / E ratio of the coated and heat-treated samples is significantly higher than that of the uncoated CoCrMo. The H / E value of the sample is the highest at an annealing temperature of 900°C, which is beneficial to improving the wear resistance of the sample. In addition, the H / E value of the 4.3μm tantalum coating is slightly higher than that of the 9.5μm tantalum coating sample, indicating that the 4.3μm tantalum coating sample is relatively more conducive to improving the wear resistance of the substrate than the 9.5μm tantalum coating sample. 4. Effect of heat treatment on coating adhesion

[0094] 4.1 Effect of heat treatment on the adhesion of TC4 sample coating

[0095] Fig.12 and 13 The scratch test curve of the tantalum coating Ti-6Al-4V and the surface morphology of the critical load position when the coating is damaged are shown respectively. Fig.12 Tantalum coating 4.3μm, Fig.13Figure 9.5μm, where 12(a) and Fig.13 (a) represents the scratch failure load before heat treatment, Fig.12 (b)-(d) and Fig.13 (b)-(d) show the critical load and sliding distance of the tantalum coating at annealing temperatures of 650℃, 750℃ and 850℃. Fig.12 and 13 (e) gives the sliding distance and critical load of the sample during wear.

[0096] exist Fig.12 In (a), the coating peeling off on both sides of the scratch of the TC4 sample was observed, and the critical load Lc was 6.5N. Fig.12 The bonding strengths observed in (b)-(d) are 16.3N, 20.8N, and 3.9N, respectively, indicating that heat treatment has a significant effect on the adhesion of the tantalum film. As the heat treatment temperature increases, the bonding strength of the coating increases first and then decreases. Fig.12 (c)) shows the best bonding strength, and continuous cracking and sliding of the coating are observed, and no peeling of the film on both sides is found. Fig.13 There is a similar trend change, and the adhesion and sliding distance of the coating are relative to Fig.12 The larger the tantalum film thickness, the greater the hardening. The results show that the tantalum layer annealed at about 750℃ has better bonding strength than the samples annealed at other temperatures.

[0097] 4.2 Effect of heat treatment on the adhesion of CoCrMo samples

[0098] Fig.14 and 15 The scratch tester curves and corresponding scratch morphologies of CoCrMo samples with Ta coating thickness of 4.3μm and 9.5μm at different heat treatment temperatures and the surface morphology of the critical load position when the coating is damaged are shown, including (a) room temperature; (b) 650℃; (c) 750℃; (d) 850℃ and (e) critical scratch distance and load.

[0099] The bonding strength of the coating is determined by the critical load (Lc) for film delamination on the scratch track, e.g. Fig.14 (a) and Fig.15 As shown in (a), for the coating without heat treatment, the initial peeling of the coating occurs at 0.54mm and 0.82mm, and the corresponding critical loads are 6.3N and 9.0N, respectively. It is observed that the coating falls off over a large area, exposing the substrate of the CoCrMo alloy. The thin Ta coating is easily brittle fractured under normal load, which indicates that the bonding strength of the coating is not very good and needs to be improved. The bonding strength of the coating is significantly improved after heat treatment ( Fig.14 (bd) and Fig.15 (bd)). With the increase of annealing temperature (800℃, 900℃ and 1000℃), the critical load of the coating first increases and then decreases, indicating that the bonding strength is optimal at the annealing temperature of 900℃. This is because the Ta coating initially diffuses with the matrix elements at this temperature, which greatly reduces the stress at the bonding interface and improves the bonding strength of the interface. In addition, the bonding strength of the annealed coating is significantly higher than that of the CoCrMo coated sample. It can be seen that the annealing process significantly improves the bonding strength of the coating, and the critical load of the 9.5μm coating after coating and heat treatment is higher than that of the 4.3μm coating ( Fig.14 )and Fig.15 )). Due to the increase in Ta film thickness, the surface hardening is slightly enhanced and has higher scratch resistance. Therefore, with a certain increase in coating thickness, the bonding strength of the coating is slightly enhanced. 5. Effect of heat treatment on the friction properties of sample surfaces

[0100] 5.1 Effect of heat treatment on the friction properties of TC4 sample coating

[0101] Fig.16 and 17 The friction coefficient curves of TC4 samples with 4.3 μm Ta and 9.5 μm Ta deposited at different heat treatment temperatures are shown. Fig.16 and 17 It can be seen that the friction curve of the bare TC4 titanium alloy substrate fluctuates with the increase of friction time, showing strong vibration, and its average friction coefficient is about 0.796 at most. Compared with TC4 alloy, the titanium alloy sample after tantalum coating heat treatment shows a lower friction coefficient and a more stable friction curve with less fluctuation. Among them, the smallest average friction coefficient (0.43 and 0.32) is shown at the heat treatment temperature of 750℃, the friction curve fluctuates the least, and shows the highest wear resistance.

[0102] 5.2 Effect of heat treatment on the friction properties of CoCrMo sample coating

[0103] Fig.18 and 19 The friction coefficient curves of the cobalt-chromium-molybdenum samples plated with 4.3μm Ta and 9.5μm Ta at different heat treatment temperatures under dry ball reciprocating loading at room temperature are shown. Fig.18 and Fig.19 The relationship between the coefficient of friction (COF) and the accumulated sliding time of the bare substrate, the as-deposited Ta coating, and the samples at different annealing temperatures is shown. Fig.18 and Fig.19It can be seen that the COF value of the bare CoCrMo alloy is the highest, which is 0.5±0.1. The generation of friction heat during dry sliding causes the alloy surface to soften, increasing the friction contact surface of the grinding ball, indicating that its wear resistance is poor. Compared with the CoCrMo alloy, the friction curves of the samples plated with tantalum and heat treated have less fluctuation and are more stable, and show lower COF values ​​than the Co-based alloy. Among them, the 4.3μm and 9.5μm Ta coatings show the smallest COF average values ​​(0.399 and 0.406) and smaller fluctuations at annealing temperatures of 800℃ and 900℃, showing better wear resistance.

[0104] In general, when the TC4 tantalum is heat treated at 750℃, the coating and substrate have better bonding strength, and the wear resistance is also improved accordingly. Cobalt-chromium-molybdenum tantalum plating has better comprehensive mechanical properties after heat treatment at 900℃.

[0105] 6. Corrosion performance test

[0106] 6.1TC4 sample

[0107] Fig. 20 (a) and 21(a) are the electrochemical potentiodynamic polarization curves of 4.3μm Ta, 9.5μm Ta coated and uncoated TC4 samples in SBF solution at different heat treatment temperatures, respectively. Fig. 20 (b) and 21(b) are the corresponding Nyquist plots. Table 3 shows the test results of the corrosion test Ecorr, which is obtained from the polarization curve by Tafel extrapolation. The results show that compared with the bare TC4 titanium alloy substrate, the coated sample shows a higher Ecorr. Generally speaking, the higher the corrosion potential, the better the corrosion resistance of the material. The sample results show that the coating of all TC4 coated samples at different heat treatment temperatures has excellent anti-corrosion performance for TC4 alloy and improves the chemical stability of the implant in body fluids. Among them, the corrosion current density is the smallest at the heat treatment temperature of 750℃, showing the best corrosion resistance. This is mainly due to the fact that at the 750℃ annealing temperature, the microporous defects of the coating are reduced, the density of the coating is improved, and the passage of the corrosive liquid to the substrate is effectively blocked, thereby significantly improving the corrosion resistance of the TC4 titanium alloy substrate. In order to further clarify the effect of the coating after different heat treatments on the corrosion resistance of the TC4 titanium alloy, the electrochemical impedance spectra of the coated and uncoated titanium alloys were tested. The Nyquist plot shows that the radius of curvature of the tantalum coating at the annealing temperature of 750℃ is large, showing good corrosion resistance. The results are consistent with the polarization curve, indicating that the tantalum coating at the annealing temperature of 750℃ has excellent corrosion resistance. The coating at the annealing temperature of 850℃ shows the largest radius of curvature. It may be that at a high temperature, the surface of the coating is oxidized to form an oxide layer, and in the absence of voltage, the oxide layer is more likely to play an insulating role, making the measured results larger.

[0108] 6.2 Cobalt-chromium-molybdenum samples

[0109] Fig. 22 and Fig.23 The potentiodynamic polarization curves of 4.3 μm Ta and 9.5 μm Ta CoCrMo samples at different heat treatment temperatures in SBF solution are shown in Table 3. Fig. 22 and 23 The electrochemical corrosion potential and corrosion current density obtained by the Tafel extrapolation method of the dynamic potentiodynamic curve are shown. The bare CoCrMo alloy substrate has the lowest corrosion potential and the highest corrosion current density. The coated and heat-treated samples have higher corrosion potential and lower corrosion current density, and the current density is reduced by 2-3 orders of magnitude, which significantly improves the corrosion performance of the CoCrMo alloy substrate.

[0110] Table 3 Corrosion potential Ecorr of uncoated or coated TC4 and cobalt-chromium-molybdenum samples

[0111]

[0112]

[0113] VII. Effect of coating on sample biocompatibility

[0114] 7.1 Cytotoxicity of TC4 titanium alloy samples

[0115] Cytotoxicity experiments were performed using the MTT colorimetric method. Cell culture medium was prepared using 90% high glucose medium (DMEM) + 10% fetal bovine serum (FBS) + 1% penicillin-streptomycin. Mouse embryonic osteoblasts (MC3T3-E1) were cultured at 25 cm 2 The cells were cultured in square breathable cap and beveled cell culture flasks, which were placed in a humidified incubator at 37°C containing 5% CO2.

[0116] Before the cell experiment, all samples were cleaned with 75% alcohol and dried in a vacuum chamber overnight, and then sterilized with ultraviolet light on a clean bench for 1 day. 2 ) and DMEM solution volume (mL) in a ratio of 2:3 into a 100 ml centrifuge tube and let it stand for 3 days. Then take out the sample and add DMEM to prepare three different extracts of 100%, 50% and 25%, and put them in the refrigerator for use.

[0117] The cytotoxicity of the extracts of bare titanium alloy substrate and Ta coating was studied by MTT colorimetry. MC3T3-E1 cells were seeded in 96-well cell culture plates at a seeding density of 10 5 / mL, placed in an incubator for 1 day, the original cell culture medium was replaced with extracts of different concentrations, 10 μL of MTT was added to each well after 1, 2, and 3 days, and the wells were left to stand for 4 hours. The culture medium was aspirated from each well, and 150 μL of dimethyl sulfoxide was added. The 96-well plate was gently shaken horizontally in the dark, and the absorbance value (λ=550 nm) was measured with an enzyme marker. The relative cell proliferation rate (RGR) was calculated according to the following formula:

[0118]

[0119] Where: ODt is the absorbance value of the experimental group, ODn is the absorbance value of the negative control group

[0120] Fig.24 and 25 The relative growth rate (RGR) of MC3T3-E1 cells inoculated on different TC4 titanium alloy specimens immersed in extracts for 1, 2 and 3 days is shown: (a) 1 day; (b) 2 days; (c) 3 days.

[0121] Generally speaking, when RGR≥75%, the sample is considered to have no toxicity to cells. Fig.24 and Fig.25 It can be seen that the RGR value of the TC4 titanium alloy coated with tantalum coating at different leaching solution concentrations is higher than that of the TC4 titanium alloy matrix. Especially in the 100% leaching solution, the RGR value of the TC4 titanium alloy matrix without coating is <70%, showing obvious cytotoxicity to MC3T3-E1. This may be due to the presence of Al in the titanium alloy matrix. 3+ and V 5+ The release of toxic metal ions such as Fig.24 (a)-(b) As the heat treatment temperature increases, the RGR value shows an increasing trend, and Fig.25 It can be observed that the samples showed high RGR values ​​at annealing temperatures of 750℃ and 850℃, indicating that the annealed samples improved the cell compatibility of TC4 titanium alloy and also effectively inhibited the release of toxic metal ions.

[0122] 7.2 Cell attachment experiment of Cobalt-Chromium-Molybdenum samples

[0123] Before cell recovery, first prepare the cell culture medium, which is formulated as (90% incomplete high-glucose medium DMEM + 10% fetal bovine serum FBS + 1% penicillin-streptomycin). Take out mouse fibroblasts (L929) and osteoblasts (MC3T3-E1) from the freezing tubes in the cold box, heat them to 37°C in a water bath, and thaw them at a constant temperature. After the cells are thawed, first spray the outer wall of the freezing tube with 75% alcohol for disinfection, and place it on an operating table that has been disinfected with ultraviolet light in advance. Move the thawed cell solution to a 50ml cell culture bottle, add 10ml of cell culture fluid, and shake it gently to evenly distribute the cells. Finally, place it in a constant temperature box with 5% CO2 and 37°C for culture. After 6 hours, observe the cell morphology under a microscope and replace the cell culture fluid. Thereafter, replace the cell culture medium every 24 hours.

[0124] After 2-3 days of cell culture, when the cell density reaches 80%-90%, cell subculture can be performed. Place the cell culture bottle on the operating table, pour out the culture medium, wash with 6ml PBS (3ml twice), add 1ml trypsin to remove the cell wall, place in 5% CO2, and culture in a 37℃ constant temperature box for about 2min. Take out and shake gently, add 10ml cell culture medium, gently blow the cell solution 100 times to make the cells evenly distributed, take 5.5mL of cell suspension, transfer to another bottle of cell culture bottle and mark it, put it together in a 5% CO2, 37℃ incubator, and change the cell culture medium once every 24 hours.

[0125] Before cell plating, pre-treat the samples. After ultrasonic cleaning with alcohol for 5 minutes, place the samples on the operating table in 75% alcohol for UV disinfection for 24 hours, take them out and place them on the operating table to dry. After L929 cells are completely attached to the wall and grow in a culture environment of 5% CO2 and 37°C, the cells can be counted on the counter (4×4 grids) and the average value is calculated by taking 4 times. If the number of cells is sufficient, the cells can be plated. L929 cells are inoculated on a 12-well cell culture plate with a cell density of 10 5 cell / ml and cultured in an incubator for 72 hours.

[0126] Take out the sample and cell fluid, place the well plate cultured for 72h in a 5% CO2, 37°C incubator on the operating table, remove the cell fluid from the well plate, wash three times with PBS, add paraformaldehyde to facilitate cell fixation, remove paraformaldehyde after 0.5h, and wash three times with PBS. Before staining the cells, turn off the lights in the laboratory, add 300μL of fluorescein isothiocyanate (FITC) to stain the cytoskeleton, and remove FITC after 1h. Wash three times with PBS again, add 300μL of 4,6-diamidino-2-phenylindole (DAPI), i.e., blue fluorescent dye, and gently shake the 12-well culture plate after 1h to ensure that the dye is tiled at the bottom of the culture well. Then perform biological laser confocal photography and high-content analysis, where green is the cytoskeleton and blue is the nucleus.

[0127] Fig.26 and Fig. 27 The cell staining morphology and cell proliferation rate of L929 cells and MC3T3-E1 cells after 72 hours of culture in coated and uncoated CoCrMo alloy samples are shown. The cytoskeleton morphology above corresponds to the cell nucleus in the figure below. L929 cells are spindle-shaped and polygonal, while MC3T3-E1 cells are normal long elliptical and irregular. It can be seen from the figure that the number of cells on the surface of the bare CoCrMo alloy substrate is small, while the number of cells on the surface of the sample after coating and heat treatment increases significantly, indicating that Ta coating can promote the growth of cells on the surface of CoCrMo alloy, and when the heat treatment temperature is 900℃, the number of cells on the surface of the coated sample increases, indicating that heat treatment further improves the biocompatibility of the CoCrMo alloy matrix.

[0128] In summary, TC4 tantalum-plated samples heat treated at 750°C have good corrosion resistance and good bonding strength, while TC4 samples annealed at 750°C and 850°C show good biocompatibility with MC3T3-E1. Cobalt-chromium-molybdenum tantalum-plated samples heat treated at 900°C have good bonding strength, corrosion resistance and good biocompatibility.

Claims

1. A method for preparing an orthopedic implant having a tantalum coating on its surface, characterized in that: Includes steps: Step 1, cleaning the implant device to be plated; Step 2, using a pure Ta target material to perform sputtering coating on the device surface under vacuum conditions; Step 3, the coated device is subjected to vacuum heat treatment to obtain a finished product. When the implant device substrate is cobalt-chromium-molybdenum alloy, the heat treatment temperature is 875-925°C; the vacuum degree of the heat treatment is <1.0×10 -2 Pa, heat treatment time is 1-5h; The thickness of the Ta coating is 1-20 μm, and the bonding strength between the tantalum coating and the substrate is measured by a scratch tester and the value is not less than 15N.

2. The method for preparing an orthopedic implant having a tantalum coating on the surface according to claim 1, characterized in that: In step 1, inert gas plasma cleaning is used for cleaning.

3. The method for preparing an orthopedic implant having a tantalum coating on the surface according to claim 1, characterized in that: The sputtering conditions include: the distance between the device surface and the target center is 50-150 mm, and the device is continuously rotated during the sputtering process; When a target with a diameter of 100 mm is used, the power applied to the target is 300-500 W, and the corresponding sputtering current is 0.5-1.5 A; the coating time is 4-8 hours.

4. The method for preparing an orthopedic implant having a tantalum coating on the surface according to claim 1, characterized in that: During the coating process, the orthopedic implant is heated and negative bias is applied, the heating temperature is 150-210°C, and the bias voltage is -200 to -100V.

5. An implant having a tantalum coating on its surface, characterized in that: A tantalum coating is plated on the surface of an implant using the method described in any one of claims 1 to 4.

6. The implant with a tantalum coating on the surface according to claim 5, characterized in that: The bonding strength between the tantalum coating and the substrate is measured by a scratch tester and has a value of not less than 15N.

Citation Information

Patent Citations

  • High-tissue-affinity corrosion-resisting implant tooth and manufacturing method thereof

    CN106691609A

  • Tantalum coating, preparation method thereof and dental implant

    CN112813404A

  • Method for plating tantalum on TiNi alloy surface

    CN101497988A